Multisensory-Mediated Auditory Localization - Bolognini, Nadia; Leor, Fabrizio; Passamonti, Claudia; Stein, Barry E; Làdavas, Elisabetta (Perception (London), 2007)
Multisensory integration is a powerful mechanism for maximizing sensitivity to sensory events. We examined its effects on auditory localization in healthy human subjects. The specific objective was to test whether the relative intensity and location of a seemingly irrelevant visual stimulus would influence auditory localization in accordance with the inverse effectiveness and spatial rules of multisensory integration that have been developed from neurophysiological studies with animals [Stein and Meredith, 1993 The Merging of the Senses (Cambridge, MA: MIT Press)]. Subjects were asked to localize a sound in one condition in which a neutral visual stimulus was either above threshold (supra-threshold) or at threshold. In both cases the spatial disparity of the visual and auditory stimuli was systematically varied. The results reveal that stimulus salience is a critical factor in determining the effect of a neutral visual cue on auditory localization. Visual bias and, hence, perceptual translocation of the auditory stimulus appeared when the visual stimulus was supra-threshold, regardless of its location. However, this was not the case when the visual stimulus was at threshold. In this case, the influence of the visual cue was apparent only when the two cues were spatially coincident and resulted in an enhancement of stimulus localization. These data suggest that the brain uses multiple strategies to integrate multisensory information.